1999
DOI: 10.1007/s004680050211
|View full text |Cite
|
Sign up to set email alerts
|

Response of photosynthesis of different plant functional types to environmental changes along Northeast China Transect

Abstract: Net photosynthesis (P n ), transpiration (E), stomatal conductance (g s ), internal CO 2 concentration (C i ), and water use efficiency (WUE) were examined on 215 species from eight plant functional types (PFTs) along a precipitation gradient in northeast China (the Northeast China Transect, or NECT). Among the eight PFTs, meadow steppe grasses had the highest rates of net photosynthesis and forest grasses the lowest and the following order of P n was noted: meadow steppe grasses >typical steppe grasses >stepp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 23 publications
1
30
0
Order By: Relevance
“…2) may be associated with high photosynthetic rates (Jiang et al 1999) and accumulation of photosynthesis-soluble sugars (Walter 1974;Lawlor and Cornic 2002). It has been well documented that accumulated osmolytes derived from photosynthesis-soluble sugars induce low osmotic potential in some species (Guicherd et al 1997;Alarc贸n et al 1993;Mendes et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…2) may be associated with high photosynthetic rates (Jiang et al 1999) and accumulation of photosynthesis-soluble sugars (Walter 1974;Lawlor and Cornic 2002). It has been well documented that accumulated osmolytes derived from photosynthesis-soluble sugars induce low osmotic potential in some species (Guicherd et al 1997;Alarc贸n et al 1993;Mendes et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…All species were classified into C 3 and C 4 categories on the basis of the photosynthetic pathways from the previous identifications (Yin & Li, 1997;Yin & Wang, 1997;Jiang et al, 1999;Tang, 1999). The PFTs of grass, shrub, and forb were classified according to the information from field investigation and herbarium.…”
Section: Pftsmentioning
confidence: 99%
“…Other PFTs, such as shrubs and forbs, were poorly considered. Jiang et al (1999) reported the response of photosynthesis of eight PFTs to environmental changes on the NECT, but there was lack of quantitative analyses of relationships between PFTs and climate.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Most transect studies focused on the effects of climatic and geographical variations on ecosystem production and vegetation distribution (Li, 1995;Zhang et al, 1997;Cao & Woodward, 1998;Gao et al, 2000;Ni & Zhang, 2000;). Some have tested the response of photosynthesis of plant functional types to climatic changes along terrestrial transect (Jiang et al, 1999;Wang, 2002). Few have looked at the influences of large-scale climatic changes or geography gradients on plant morphology (Wang, 2001) and mortality (Villalba & Veblen, 1998).…”
Section: Introductionmentioning
confidence: 99%